PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN BAGI GURU SEKOLAH DASAR - Rumidjan, Rumidjan; Sumanto, Sumanto; Sukamti, Sukamti; Sugiharti, Sri (ABDIMAS PEDAGOGI, 2017)
Abstract: Elementary school teachers as professional educators who act as a facilitator in learning creativity is required to explore the potential sources and learning media that exist in the environment in order to teach students in quality. In order to be a good facilitator of elementary school (SD) teachers are expected to equip themselves with the insights and skills of the development of design and the making of learning media so that teachers can run its role well. The reality shows that elementary school teachers in the Malang subdistrict of Lowokwaru generally have difficulty in improving the quality and effectiveness of learning in each elementary school. This situation is caused by the lack of facilities and infrastructure that can support studentsâ activeness and enjoyment in learning as well because the teachers do not have enough knowledge and skills to create a fun learning media for children. Therefore, the Task Force gave Training of Learning Media Development to the teachers of SD in Subdistrict Lowokwaru Malang City in hopes to improve the effectiveness and quality of learning process in elementary school will ultimately support the achievement of educational goals in the target area.Keywords: learning media, learning qualityAbstrak: Guru SD sebagai tenaga pendidik profesional yang berperan sebagai fasilitator dalam pembelajaran dituntut kreativitasnya untuk menggali potensi sumber dan media pembelajaran yang ada di lingkungannya agar dapat membelajarkan muridnya secara berkualitas. Agar dapat jadi fasilitator yang baik guru SD diharapkan dapat membekali diri dengan wawasan dan keterampilan pengembangan desain dan pembuatan media pembelajaran sehingga guru dapat menjalankan perannya dengan baik. Kenyataannya menunjukkan bahwa para guru SD di kecamatan Lowokwaru kota Malang pada umumnya mengalami kesulitan dalam meningkatkan kwalitas dan efektivitas pembelajaran di SD masing-masing. Keadaan ini disebabkan kurangnya sarana dan prasarana yang dapar menunjang keaktifan dan kesenangan murid dalam belajar juga karena para guru belum memiliki wawasan dan keterampilan yang memadai untuk membuat media pembelajaran yang menyenangkan bagi anak. Oleh karena itu Satgas memberi Pelatihan Pembuatan Media Pembelajaran kepada Guru-guru SD Kecamatan Lowokwaru Kota Malang dengan harapan dapat meningkatkan efektivitas dan kualitas proses pembelajaran di SD pada akhirnya akan menunjang tercapainya tujuan pendidikan di daerah sasaran.Kata kunci: media pembelajaran, kualitas pembelajaran